2014
DOI: 10.1111/jdv.12561
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for palmoplantar pustular psoriasis: systematic literature review, evidence‐based recommendations and expert opinion

Abstract: Background Palmoplantar pustular psoriasis (PPPP) is a variant of psoriasis whose the association with psoriatic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 11 publications
1
45
0
5
Order By: Relevance
“…For recalcitrant disease, oral retinoids, cyclosporine, methotrexate, biological agents and anakinra have been found to be useful [3,13,15,16]. Recent recommendations suggest the use of biologics only in patients with concurrent psoriatic arthritis results of the use of such agents for PPPP are conflicting, and these medications confer significant side effects including immunosuppression, bone marrow suppression and liver damage [16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…For recalcitrant disease, oral retinoids, cyclosporine, methotrexate, biological agents and anakinra have been found to be useful [3,13,15,16]. Recent recommendations suggest the use of biologics only in patients with concurrent psoriatic arthritis results of the use of such agents for PPPP are conflicting, and these medications confer significant side effects including immunosuppression, bone marrow suppression and liver damage [16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…Excimer‐Licht). Dieses konnte, neben der gezielten Behandlung von einzelnen Psoriasisplaques und etwas geringerer Wirkung bei der palmoplantaren pustulösen Psoriasis , auch bei der atopischen Dermatitis und der Vitiligo erfolgreich eingesetzt werden. Ebenso ist die Excimer‐Therapie bei der Alopecia areata des Erwachsenen und unter strenger Indikationsstellung bei Jugendlichen wirksam einsetzbar.…”
Section: Uv‐b‐phototherapieunclassified
“…We included patients who had been recalcitrant to other treatments, including topical corticosteroids, calcineurin inhibitors, and light therapy with an average disease duration lasting 47 months. To avoid biasing the results, patients with clinically suspected palmoplantar psoriasis were excluded from the study, as this disease has previously been shown to be responsive to excimer laser therapy . Patients were excluded based on disease morphology as well as the absence of associated skin or nail manifestations of psoriasis.…”
Section: Methodsmentioning
confidence: 99%